Effects of Fe-S-As coupled redox processes on arsenic mobilization in shallow aquifers of Datong Basin, northern China. (June 2018) - Zhang, Junwen; Ma, Teng; Yan, Yani; Xie, Xianjun; Abass, Olusegun K.; Liu, Congqiang; Zhao, Zhiqi; Wang, Zhizhen
Abstract: High arsenic groundwater generally coexists with elevated Fe 2+ concentrations (mg L −1 levels) under reducing conditions, but an explanation for the extremely high arsenic (up to ∼2690) concentrations at very low Fe 2+ (i.e., μg L −1 levels) in groundwater of Datong Basin remains elusive. Field groundwater investigation and laboratory microcosm experiments were implemented in this study. The field groundwater was characterized by weakly alkaline (pH 7.69 to 8.34) and reducing conditions (Eh −221.7 to −31.9 mV) and arsenic concentration averages at 697 μg L −1 . Acinetobacter (5.9–51.3%), Desulfosporosinus (4.6–30.2%), Brevundimonas (3.9–19%) and Pseudomonas (3.2–14.6%) were identified as the dominant genera in the bacterial communities. Bacterially mediated arsenate reduction, Fe(III) reduction, and sulfate reduction are processes occurring (or having previously occurred) in the groundwater. Results from incubation experiment (27 d) revealed that nitrate, arsenate, and Fe(III)/sulfate reduced sequentially with time under anoxic conditions, while Fe(III) and sulfate reduction processes had no obvious differences, occurring almost simultaneously. Moreover, low Fe 2+ concentrations were attributed to initially high pH conditions, which relatively retarded Fe(III) reduction. In addition, arsenic behavior in relation to groundwater redox conditions, matrices, and solution chemistry were elaborated. Bacterial arsenate reduction process proceeded before Fe(III) and sulfate reduction in the incubation experiment, and the total arsenic concentration (dominated by arsenite) gradually increased from ∼7 to 115 μg L −1 as arsenate was reduced. Accordingly, bacterially mediated reductive desorption of arsenate is identified as the main process controlling arsenic mobility, while Fe(III) reduction coupled with sulfate reduction are secondary processes that have also contributed to arsenic enrichment in the study site. Overall, this study provide important insights into the mechanism controlling arsenic mobility under weakly alkaline and reducing conditions, and furnishes that arsenate reduction by bacteria play a major role leading to high accumulation of desorbed arsenite in groundwater. Graphical abstract: Image 1 Highlights: Bacterial communities corresponds to hydrochemical features of high As(III) and HS − . Bacterially mediated Fe(III) reduction inhibited by relatively high pH conditions. Reductive desorption of As(V) is the main reason for As mobility in study area. Fe(III) reduction coupled with sulfate reduction both contribute to As mobility. Abstract : Reductive desorption of As(V) is the main reason for As mobility, while Fe(III) reduction coupled with sulfate reduction are secondary processes in the study site.